RSS - a decade of collective security in the Caribbean. - GRIFFITH, Ivelaw L. (1992)
Discusses the structure and operations of the Regional Security System. Notes that the RSS is a mechanism with limited utility - a security half-way house, dependent on the interests and support of outside powers, and pre-occupied with the political and other challenges facing its members.